The Relationship Between Perceived Workload and Perceived Organizational Support and Work Life Balance Among Electronic Service Employees in Bojonegoro - Muhammad Erick Aldiansyah; Pratama, Rio Chandra; Maghfiroh, Amalia Ma'rifatul (Journal of Information System, Technology and Engineering, 2023)
This research aims to determine whether there is a relationship between perceptions of organizational support and perceptions of workload and work-life balance among electronic service employees in Bojonegoro. A quantitative approach was used in this research. The sampling technique used was saturated sampling using electronic service employees in Bojonegoro who were tasked with handling electronic service in workshops and on call, totaling 30 employees. The instruments used in collecting data were a scale of perceptions of organizational support, a workload scale, and a work-life balance scale, which were presented in the form of a Likert scale. Hypothesis testing the data analysis method used is the multiple correlation test using SPSS 22 software. Based on the results of the analysis, it can be seen that the significance value (p value) is 0.002 with a significance level of 0.05. So, it can be concluded that p < 0.05. From the calculation results, the calculated F is obtained at 5,881. The F table value with three variables and N=30 respondents obtained a value of 3.316. So that F count > F table. Thus, it can be concluded that one research hypothesis can be accepted, namely that there is a relationship between perceptions of organizational support and perceptions of workload and work-life balance. At the correlation coefficient level, it is known that this research has a correlation coefficient value that is included in the moderate relationship level, namely 0.551. This means that there is a relationship between perceived organizational support, perceived workload, and work-life balance.